C1q/TNF‐related protein 9 inhibits the cholesterol‐induced Vascular smooth muscle cell phenotype switch and cell dysfunction by activating AMP‐dependent kinase. Issue 11 (19th May 2017) - Liu, Qi; Zhang, Hui; Lin, Jiale; Zhang, Ruoxi; Chen, Shuyuan; Liu, Wei; Sun, Meng; Du, Wenjuan; Hou, Jingbo; Yu, Bo
Abstract: Vascular smooth muscle cells (VSMCs) switch to macrophage‐like cells after cholesterol loading, and this change may play an important role in the progression of atherosclerosis. C1q/TNF‐related protein 9 (CTRP9) is a recently discovered adipokine that has been shown to have beneficial effects on glucose metabolism and vascular function, particularly in regard to cardiovascular disease. The question of whether CTRP9 can protect VSMCs from cholesterol damage has not been addressed. In this study, the impact of CTRP9 on cholesterol‐damaged VSMCs was observed. Our data show that in cholesterol‐treated VSMCs, CTRP9 significantly reversed the cholesterol‐induced increases in pro‐inflammatory factor secretion, monocyte adhesion, cholesterol uptake and expression of the macrophage marker CD68. Meanwhile, CTRP9 prevented the cholesterol‐induced activation of the TLR4–MyD88–p65 pathway and upregulated the expression of proteins important for cholesterol efflux. Mechanistically, as siRNA‐induced selective gene ablation of AMPKα1 abolished these effects of CTRP9, we concluded that CTRP9 achieves these protective effects in VSMCs through the AMP‐dependent kinase (AMPK) pathway.